Effects of Citrus Overwintering Predators, Host Plant Phenology and Environmental Variables on Aphid Infestation Dynamics in Clementine Citrus - Bouvet, Juan Pedro Raúl; Urbaneja, Alberto; Monzó, César (Oxford, 2020)
The Spirea citrus aphid, Aphis spiraecola Patch, and the cotton aphid, Aphis gossypii Glover (Hemiptera: Aphididae), are key pests of clementine mandarines in the Mediterranean basin. Severity of aphid infestations is determined by environmental variables, host plant phenology patterns, and the biological control exerted by their associated natural enemies. However, there is no information about the role these limiting and regulating factors play. Aphid densities, citrus phenology, and associated predators that overwinter in the crop were monitored weekly throughout two flush growth periods (February to July) in four clementine mandarin groves; relationships between these parameters and environmental variables (temperature and precipitation) were studied. Our results show exponential increase in aphid infestation levels to coincide with citrus phenological stages B3 and B4; shoots offer more space and nutritional resources for colony growth at these stages. Duration of these phenological stages, which was mediated by mean temperature, seems to importantly determine the severity of aphid infestations in the groves. Among those studied, the micro-coccinellids, mostly Scymnus species, were the only group of predators with the ability to efficiently regulate aphid populations. These natural enemies had the highest temporal and spatial demographic stability. Aphid regulation success was only achieved through early presence of natural enemies in the grove, at the aphid colonization phase. Our results suggest that conservation strategies aimed at preserving and enhancing Scymnus sp. populations may make an important contribution to the future success of the biological control of these key citrus pests